Estimated impact of maternal vaccination on global paediatric influenza-related in-hospital mortality: A retrospective case series. (July 2021) - Löwensteyn, Yvette N; Nair, Harish; Nunes, Marta C; van Roessel, Ichelle; Vernooij, Femke S; Willemsen, Joukje; Bont, Louis J; Mazur, Natalie I; Thorburn, Kentigern; Nunes, Marta; Chawana, Richard; et al.
Abstract: Background: Influenza virus infection is an important cause of under-five mortality. Maternal vaccination protects children younger than 3 months of age from influenza infection. However, it is unknown to what extent paediatric influenza-related mortality may be prevented by a maternal vaccine since global age-stratified mortality data are lacking. Methods: We invited clinicians and researchers to share clinical and demographic characteristics from children younger than 5 years who died with laboratory-confirmed influenza infection between January 1, 1995 and March 31, 2020. We evaluated the potential impact of maternal vaccination by estimating the number of children younger than 3 months with in-hospital influenza-related death using published global mortality estimates. Findings: We included 314 children from 31 countries. Comorbidities were present in 166 (53%) children and 41 (13%) children were born prematurely. Median age at death was 8·6 (IQR 4·5–16·6), 11·5 (IQR 4·3–24·0), and 15·5 (IQR 7·4–27·0) months for children from low- and lower-middle-income countries (LMICs), upper-middle-income countries (UMICs), and high-income countries (HICs), respectively. The proportion of children younger than 3 months at time of death was 17% in LMICs, 12% in UMICs, and 7% in HICs. We estimated that 3339 annual influenza-related in-hospital deaths occur in the first 3 months of life globally. Interpretation: In our study, less than 20% of children is younger than 3 months at time of influenza-related death. Although maternal influenza vaccination may impact maternal and infant influenza disease burden, additional immunisation strategies are needed to prevent global influenza-related childhood mortality. The missing data, global coverage, and data quality in this study should be taken into consideration for further interpretation of the results. Funding: Bill & Melinda Gates Foundation.